Facial skin color assessment and proposed skin shade guide for maxillofacial prosthesis using cluster analysis in a cohort of Indian adults - Priyadarshani Gulabrao Pawar; Anjali Borle; Pradnya R. Patil; Rohit M. Patil; Priyanka S. Gadakh; Gita Rani (The Journal of Indian Prosthodontic Society)
Aim: The precise estimation and replication of skin color are crucial for maxillofacial prosthesis. The study aimed to evaluate facial skin color with a colorimeter and suggest a skin shade guide and formula for color estimation. Settings and Design: An observational study conducted in the department of prosthodontics. Materials and Methods: Study was conducted on 368 individuals of Indian origin in age range of 20–45 years. The facial skin color was assessed in malar regions using SkinColorCatch colorimetric device and individual topography angle (ITA) and CIELAB L*a*b* values were noted. Statistical Analysis Used: K-means clustering was utilized to propose a shade guide for maxillofacial prosthesis with 24 skin shades. Logistic regression analysis was conducted to propose a formula to estimate skin shade of the individuals. Results: Based on cluster analysis, 368 subjects were divided into three clusters with similar characteristic as Cluster 1 with dark skin color in 88 (23.91%) subjects, Cluster 2 with medium skin color in 224 (60.87%) subjects, and Cluster 3 with light skin color in 56 (15.22%) subjects. The mean ITA and L*a*b* values for cluster 1 were −47.04° ±14.77°, 34.53 ± 4.31, 8.55 ± 2, 11.42 ± 3.7033, respectively. The mean ITA angle and L*a*b* values for Cluster 2 were 4.29° ±11.34° 51.67 ± 3.42, 8.79 ± 3.13, 21.36 ± 2.38, respectively. The mean ITA and L*a*b* values for Cluster 3 were 34.65 ± 4.29°, 62.66 ± 3.08, 6.53 ± 1.79, 17.73 ± 2.39, respectively. The proposed shade guide comprised a total of 24 different shades that were categorized into three primary colors according to three distinct clusters, each of which was further broken down into eight subclusters containing various shades within each cluster. Logistic regression analysis gave an equation as follows: Y =12.43 + 0.186X (Y = Predicted skin color, X = ITA angle). Conclusions: Twenty-four facial skin shade tabs have been proposed based on ITA angle and CIELAB values. This comprehensive approach to categorize the shades will ensure a detailed and organized system for selecting and matching colors in maxillofacial prosthesis.